Cardiac and neurological complications post COVID-19 vaccination: a systematic review of case reports and case series - Lee, Kai Wei; Yap, Sook Fan; Amin-Nordin, Syafinaz; Ngeow, Yun Fong (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Following mass vaccinations for the control of the COVID-19 epidemic, a spectrum of cardiac and neurological disorders was reported among vaccinated individuals. This study examined the range of complications documented and factors related to their occurrence. Three electronic databases were searched for case reports and case series with descriptions of cardiac and/or neurological complications in COVID-19 vaccine recipients. A total of 698 vaccinees were included in this review, of which 259 (37.1%) had cardiac and 439 (62.9%) had neurological complications. Inflammatory conditions were the commonest among the cardiac complications; while polyneuropathy, demyelinating diseases and cerebrovascular disorders were the more common neurological complications. The mean age of those with cardiac complications (33.8 years) was much younger than those with neurological complications (49.7 years). There was no notable difference in the gender distribution between these two groups of vaccine recipients. mRNA vaccines (all brands) were associated with almost 90.0% of the cardiac complications, whereas viral vector vaccines were associated with slightly over half (52.6%) of the neurological complications. With regard to the dose, cardiac complications were more common after the second (69.1%), whereas neurological complications were more common after the first dose (63.6%). The majority of the cases had an uncomplicated clinical course. Nevertheless, 5.9% of cases with neurological complications and 2.5% of those with cardiac complications were fatal, underscoring the significance of the consistent surveillance and vigilant monitoring of vaccinated individuals to mitigate these occurrences.